Structural and electrical properties of Mg Silicide thin films deposited by RF sputtering. (2020) - Gupta, Suniksha; Howlader, Smita; Sharma, Atul; Banerjee, M.K.; Asokan, K.; Sachdev, K.
Highlights: Mg2 Si thin film deposited by radio frequency sputtering technique at 90Watt power by a new approach. Good electrical conductivity (10 3 S/m) was observed for Mg2 Si thin films. There is further need to optimize the properties of Mg2 Si thin films so as to get a good thermoelectric thin film. Abstract: Mg2 Si based thin films are a promising candidate for thermoelectric applications in the mid temperature range. The main advantages of these films are their low density, abundance of the elements used, good stability and environmental friendly nature. Nano structuring is considered to be useful tool to enhance the properties and hence thin films have been studied; although fabrication of Mg2 Si thin film has been difficult due to difference in properties of magnesium and silicon. Semiconducting Mg2 Si thin films were deposited on silicon substrate by radio frequency magnetron sputtering at low substrate temperature following a distinct approach. X-ray diffraction (XRD) and Field – Emission Scanning Electron Microscopy (FE-SEM) with EDS were done to study the phases, elemental composition and microstructure of these films. XRD results showed single phase Mg2 Si formation. SEM results revealed granular nature of films and no cracks were observed. XPS was employed to study the chemical composition of films. The thin films were studied for their electrical transport behaviour through I-V and Hall measurements. Maximum conductivity of Mg2 Si thin films was found to be ∼ 10 3 S/m and a carrier concentration of 5.14 + 19/cm 3 was obtained for 300 nm thick film. The films showed n type nature.